Binary relation of the telluric and the temporal in Cuadernos de Tambillo by Segundo Cancino - Caballero Delgado, Gabriela (2021)
Currently, there is a growing interest in studying the close relationship that exists between time and space to construct the consciousness of the subjects and reality (in this case, imaginative). In this article we approach the binary relation of these elements as a way to approach, from its expressive nature, the symbolic system that founds the imaginary universe of the book Cuadernos de Tambillo and to make emerge the lyrical characters, making visible their complex network of relations.